Liver tests increase on abiraterone acetate in men with metastatic prostate cancer: Natural history, management and outcome. (April 2020) - Colomba, Emeline; Marret, Grégoire; Baciarello, Giulia; Lavaud, Pernelle; Massard, Christophe; Loriot, Yohann; Albiges, Laurence; Carton, Edith; Alexandre, Jérome; Huillard, Olivier; Culine, Stéphane; Fizazi, Karim
Abstract: Background: Abiraterone acetate (abiraterone) combined with prednisone is a standard of care in metastatic castration-resistant prostate cancer. Recently, benefit in overall survival was reported in metastatic castration-sensitive prostate cancer also, and an extension of indication has been granted. Abiraterone is seldom associated with liver toxicity. The clinical management and the outcome of patients with transaminase increase while on abiraterone have not been described. Patients and method: We identified 25 men with metastatic prostate cancer and liver function test disorders occurring while on abiraterone treatment from December 2009 to September 2017 in three oncology centres in France. Results: Forty-six liver disorder events occurred in 25 patients while on abiraterone treatment. The median age at liver function test increase was 67 (55–85) years. The incidence of aspartate aminotransférase (AST) (24 events) and that of alanine aminotransférase (ALT) (22 events) increases were similar. Liver toxicity was of grade 1, 2 and 3 (Common Terminology Criteria for Adverse Events. version 4) in 7 (32%), 6 (27%) and 9 (41%) patients for ALT, and in 12 (50%), 6 (25%) and 6 (25%) for AST, respectively. The median time from abiraterone initiation to the detection of liver toxicity was 7.1 (4–95) weeks. The median time from highest ALT/AST increase to normalisation was 6.2 [2–14 ] weeks. In 13 patients (52%), liver tests spontaneously returned to baseline values, while abiraterone was continued at full dose. Conclusion: Liver function test increase is a rare event that typically occurs within the first two months on abiraterone. Most patients experience normalisation of the tests, either spontaneously or after dose reduction/discontinuation. Highlights: We reported the first report focussing on liver toxicity from abiraterone and its management in real life. Most transaminase elevations in abiraterone-treated patients appears to be an infrequent event with an incidence of less than 10%. Most patients experience normalisation of tests over a median time of 2 months, either spontaneously or after dose reduction/discontinuation.